A COMPARATIVE STUDY OF NARRATIVE STRUCTURE IN THE NOVEL AND FILM “THE JUNGLE BOOK" - Hidayat, Muhammad; Weda, Sukardi (ELITERATE : Journal of English Linguistics and Literature Studies, 2021)
The aim of this research is to find out the narrative structure occurred in “The Jungle Book Novel 1894” and “The Jungle Book Film 2016” using the Caroline Denton (2007) Narrative Structure theory and Comparative Literature approach based on aspects of the narrative structure. This research used descriptive qualitative research in order to describe the aspects and its characteristics that are related to the topic. Using the Caroline Denton’s theory, the researcher used categorize the narrative structures in The Jungle Book Film 2016 and The Jungle Book Novel 1894 based 5 aspects. The researcher will also compare the narrative structures with the aspects of film in order to classify the narrative structures in two literary works to find the differences and similarities. The result of this study indicates that there are 13 similarities and 17 differences found in these two literary works based on Setting, Characters, Conflict, Climax, and Resolution aspects of narrative structure. 22 narrative structures are captured in The Jungle Book Film 2016 and 23 narrative structures are captured in The Jungle Book Novel 1894. As a conclusion for this research, the researcher is able to identify the narrative structure and compare them.